Desempenho agronômico de progênies de café arábica resistentes ao nematoide Meloidogyne exigua na região do cerrado mineiro - Pinheiro, Letícia Mendes (2021)
The nematodes from the gender Meloidogyne are a huge problem for brazilian coffee crops, because of M. exigua wide distribuition in coffee areas, and M. paranaensis and M. incognita aggressiveness. Nematodes control is complex, and to ensure productivity levels and mantain longevity of crops, planting resistant cultivars has become na importante management strategy. The aim of this work was to find C. arabica progenies that are resistant to M. exigua and present superior agronomic traits. Two experiments were installed in the cerrado mineiro region, using 34 progenies and the cultivars MGS Paraíso 2 and Catuaí Vermelho IAC 144 as controls. The progenies originate from the crossing between cultivars of the Catuaí group and the Timor Hybrid, and are in the final phase of selection. The productivity in bags of processed coffee ha-1, income of processed coffee, vegetative vigor, percentage of floating fruits, maturation, percentage of flat beans retained on sieve 16 and above, nematode population in the roots in number of eggs and juveniles gram of root-1, incidence and severity of brown eye spot on leaves and incidence of brown eye spot on fruits were evaluated. The results indicate that the progenies 2, 12, 17, 18 and the cultivar MGS Paraíso 2 showed superior behavior in Experiments 1 and 2; the progenies 2, 12, 17 and 18 had yields similar to that of Catuaí Vermelho IAC 144 but with a lower population of M. exigua in their roots and the studied progenies do not present selection potential for brown eye spot.